EGFR tyrosine kinase inhibitor Almonertinib induces apoptosis and autophagy mediated by reactive oxygen species in non-small cell lung cancer cells. (December 2021) - Ge, X; Zhang, Y; Huang, F; Wu, Y; Pang, J; Li, X; Fan, F; Liu, H; Li, S
Almonertinib, a new third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is highly selective to EGFR T790M-mutant non-small cell lung cancer (NSCLC). However, there is no available information on the form and molecular mechanism of Almonertinib-induced death in NSCLC cells. Herein, CCK-8 and colony formation assays, flow cytometry, electron microscopy, and western blots assay showed that Almonertinib inhibited NSCLC cells growth and proliferation by inducing apoptosis and autophagy which can be inhibited by a broad spectrum of caspase inhibitor Z-VAD-fmk or autophagy inhibitor chloroquine. Importantly, Almonertinib-induced autophagy was cytoprotective in NSCLC cells, and the blockade of autophagy improved cell apoptosis. In addition, Almonertinib increased reactive oxygen species (ROS) generation and clearance of ROS through pretreatment with N-acetyl-L-cysteine (NAC) inhibited the decrease of cell viability, apoptosis and increase of LC3-II induced by Almonertinib. The results of Western blot showed that both EGFR activity and downstream signaling pathways were inhibited by Almonertinib. Taken together, these findings indicated that Almonertinib induced apoptosis and autophagy by promoting ROS production in NSCLC cells.